Quasi‐2D CsPbBrxI3−x Composite Thin Films for Efficient and Stable Red Perovskite Light‐Emitting Diodes. Issue 24 (18th October 2021) - Liu, Ping; Cai, Wanqing; Zhao, Cong; Zhang, Siwei; Nie, Pengbo; Xu, Wenzhan; Meng, Hong; Fu, Hongyan; Wei, Guodan
Abstract: Remarkable progress has been achieved in perovskite light‐emitting diodes (PeLEDs) . Both green and infrared PeLEDs with external quantum efficiencies (EQEs) of over 20% are successfully developed. However, the performance of pure red PeLEDs remains challenging. Numerous efforts are explored to tune red color emission for higher emission efficiencies, but it is still suffering operation instability. Here, high‐quality and luminescent quasi‐2D (CsPbBr x I3 − x )/poly(2‐ethyl‐2‐oxazoline) (PEOXA) composite perovskite thin films are successfully fabricated via a one‐step method. Uniform and smooth perovskite thin films are obtained with photoluminescent quantum yield as high as 65% and emission is tuned from pure red to deep red (638–686 nm). Efficient PeLEDs with device structure of indium tin oxide/ZnMgO/quasi‐2D perovskite/Poly[N, N′‐bis(4‐butylphenyl)‐N, N′‐bis(phenyl)‐benzidine] (Poly‐TPD)/MoO3 /Ag have demonstrated a high EQE of 7.0% and pure red emission peak at 654 nm, with Commission Internationale de l'Éclairage coordinates of (0.703, 0.287). While the PeLEDs with an emission peak at 670 nm show a low turn‐on voltage of 1.6 V, maximum luminance of 1942 cd m −2, and maximum EQE of 9.1%. In addition, the PeLEDs achieve good spectral and operational stability with a record half‐lifetime ( T 50 ) of over 20 h at a high initial luminance of 100 cd m −2, demonstrating their good potential for display application. Abstract : High‐quality quasi‐2D perovskite/poly(2‐ethyl‐2‐oxazoline) (PEOXA) composite thin films are successfully fabricated with high photoluminescence quantum efficiency via a one‐step method. By adjusting the phenylbutanammonium iodide (PBAI) molar ratio and the PEOXA concentration, uniform and smooth perovskite thin films are obtained with high photoluminescence quantum yields and tunable emission from pure red to deep red. With an appropriate content of PBAI spacer and moderate concentration of the polymer additive PEOXA, highly efficient and stable pure‐red perovskite light‐emitting diodes (PeLEDs) are fabricated. The PeLED exhibits an ultralow turn‐on voltage of 1.6 V, maximum luminance of 1942 cd m −2, maximum EQE of 9.1%, and a record T 50 of 20 h at an initial luminance of 100 cd m −2 .